2022
DOI: 10.1186/s41235-022-00396-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of familiarity on memory for faces and mask wearing

Abstract: During the COVID-19 pandemic, the wearing of face masks became mandatory in public areas or at workplaces in many countries. While offering protection, the coverage of large parts of our face (nose, mouth and chin) may have consequences for face recognition. This seems especially important in the context of contact tracing which can require memory of familiar and unfamiliar contacts and whether they were wearing a mask. In this study, we tested how well participants perform at remembering faces and whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
1
3
1
Order By: Relevance
“…Our results show that the impact of face masks was most prominent during famous face recognition and convincingly shows the effect of familiarity in both masked and unmasked condition while previous study [11] shows the opposite trend. However recent studies [19,20] shows effect on familiarity on masked face recognition which is in line with our results. A previous study [12] also found deterioration in performance for unfamiliar face compared to familiar face matching in cross-experimental comparisons.…”
Section: Effect Of Mask On Famous and Unfamiliar Face Recognitionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results show that the impact of face masks was most prominent during famous face recognition and convincingly shows the effect of familiarity in both masked and unmasked condition while previous study [11] shows the opposite trend. However recent studies [19,20] shows effect on familiarity on masked face recognition which is in line with our results. A previous study [12] also found deterioration in performance for unfamiliar face compared to familiar face matching in cross-experimental comparisons.…”
Section: Effect Of Mask On Famous and Unfamiliar Face Recognitionsupporting
confidence: 93%
“…Furthermore, participants tended to commit more false positive errors in the face matching task when familiar faces were masked, and more false negative errors when unfamiliar faces were masked. Contrary results were observed in a more recent study [19] on the effect of face masks on familiarity. The authors demonstrate using a face memory task that face familiarity indeed plays a role in face recognition and people tend to remember familiar faces more than unfamiliar faces irrespective of face-masks.…”
Section: Introductioncontrasting
confidence: 98%
See 2 more Smart Citations
“…Despite the detrimental effect of masks on famous face identification (Wong & Estudillo, 2022 ) familiarity-detection could still occur (Carlow et al, 2022 ). Research showed that it was harder to remember not only the identity of unfamiliar faces but whether or not that unfamiliar face wore a mask (Kollenda & de Haas, 2022 ) .…”
mentioning
confidence: 99%